The application of soft skills development module through the preparation of group assignment of the UiTM professional islamic education courses, based on the leadership approach / Hamdi Rahman Mohd Yaacob ... [et al.] - Mohd Yacob, Hamdi Rahman; Yusof @ Salleh, Muhammad Yusri Yusof; Hassan, Paiz; Che Ahmat, Amin; Mohd Nor, Mohd Syukri (UiTM Press, 2020)
Managing student group assignments as one of the assessment instruments with the need to ensure student soft skills development which were mapped to the course outcomes of a program of study, is one of the major challenges to the teaching and learning process. This is because of the using of cross-curricular approach where students are not trained specifically to those skills, but at the same time the development of the skills is evaluated. For the Islamic education professional courses offered to the UiTM diploma students, there are four soft skills to be developed through the preparation of group assignments namely: teamwork; information management and the lifelong learning skills; communication skills and professional ethics. The aim of this study is to propose an appropriate module that faculty can integrate into the teaching and learning process of the courses, to ensure that every student receives training before their soft skills are evaluated. The module reliability test was conducted by five lecturers on five groups of student from four different Islamic education professional courses.